Isi Piringku Kaya akan Protein Hewani untuk Cegah Stunting - Heryani, Heni; Utami Asmarani, Sri; Setiawan, Henri; Endang Purwati, Ayu; Nurherliyany, Metty; Firmansyah, Andan; Lestari, Lusi (Kolaborasi: Jurnal Pengabdian Masyarakat, 2025)
Introduction: Stunting remains a significant nutritional issue characterized by chronic malnutrition, negatively impacting children's growth, development, and productivity throughout their lives. Proper nutrition, particularly during the first 1,000 days of life, is essential to prevent stunting. The lack of protein intake, especially from animal sources, is a major contributing factor to stunting in Indonesia. Objective: The purpose of this public service was to increase the knowledge of mothers with toddlers and health cadres regarding the importance of animal protein intake as part of the "Isi Piringku" campaign to prevent stunting in Sindangrasa Village, Ciamis Regency. Method: This public service was conducted in three stages: preparation, implementation, and evaluation. The preparation stage involved coordination with local authorities for permission and logistical arrangements. The implementation stage included pre-test knowledge assessments, an educational session using slide presentations and leaflets, and interactive discussions. The evaluation stage involved post-test assessments to measure knowledge improvement. Result: The service was attended by 30 participants, consisting of health cadres and mothers with toddlers. Pre-test results showed that 50% of participants had moderate knowledge, while 30% had low knowledge about the role of animal protein in preventing stunting. After the educational session, the percentage of participants with good knowledge increased to 53.33%, while those with moderate knowledge decreased to 46.67%. Conclusion: The findings suggest that education using slide presentations and leaflets is effective in increasing knowledge about stunting prevention through balanced nutrition. Raising awareness among mothers and health cadres is crucial in promoting behavior changes that support adequate animal protein intake to prevent stunting.